2013
DOI: 10.1093/eurjhf/hfs189
|View full text |Cite
|
Sign up to set email alerts
|

Current aspects of the spectrum of acute heart failure syndromes in a real‐life setting: the OFICA study

Abstract: AimsTo improve knowledge of epidemiological data, management, and clinical outcome of acute heart failure (AHF) in a real-life setting in France. Methods and resultsWe conducted an observational survey constituting a single-day snapshot of all unplanned hospitalizations because of AHF in 170 hospitals throughout France (the OFICA survey). A total of 1658 patients (median age 79 years, 55% male) were included. Family doctors were the first medical contact in 43% of cases, and patients were admitted through emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
112
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 41 publications
15
112
3
7
Order By: Relevance
“…2,4 The mean age is similar to that reported in a recent French single-day survey in 170 hospitals of all patients hospitalized for acute HF, 13 but 10 years older than in a recent Portuguese study enrolling patients hospitalized for acute HF only in the cardiology department of the other tertiary university hospital in the city where our study took place. In that study 73.2% of patients had HFrEF, which reflects considerable differences between the two study populations and is evidence of how observational studies provide valuable information about acute HF managed in different clinical scenarios.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…2,4 The mean age is similar to that reported in a recent French single-day survey in 170 hospitals of all patients hospitalized for acute HF, 13 but 10 years older than in a recent Portuguese study enrolling patients hospitalized for acute HF only in the cardiology department of the other tertiary university hospital in the city where our study took place. In that study 73.2% of patients had HFrEF, which reflects considerable differences between the two study populations and is evidence of how observational studies provide valuable information about acute HF managed in different clinical scenarios.…”
Section: Discussionsupporting
confidence: 81%
“…20,21 Our data on gender are in agreement with other reports showing that elderly patients hospitalized with HF are mainly women 22 and that patients with HFpEF are older and more often female than those with HFrEF. 1,5,6,8,13 HF patients managed by internists are more likely to have the characteristics of those managed by general practitioners. In the UK, the mean age of HF patients in general practice is 77 years, similar to that of our population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have reported on the in‐hospital mortality in patients with acute heart failure, which is an ample concept that includes acute decompensation of chronic heart failure, cardiogenic shock with or without pulmonary edema, right ventricular failure, and APE 3, 6, 14, 19, 20, 21. In these studies, mortality has varied from 6.4% to 17.2% and they have shown advanced age,6, 14, 19, 21 severe left ventricular dysfunction,14 acute coronary syndromes,14 admission blood pressure,6, 19, 21 renal failure,6, 19, 21 need for inotropics,19 and anemia19 as principal predictors.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, mortality has varied from 6.4% to 17.2% and they have shown advanced age,6, 14, 19, 21 severe left ventricular dysfunction,14 acute coronary syndromes,14 admission blood pressure,6, 19, 21 renal failure,6, 19, 21 need for inotropics,19 and anemia19 as principal predictors.…”
Section: Discussionmentioning
confidence: 99%